Problem solving on the Internet? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A faithful reader, Jean Revol of Technodoc in Montelimar, France, is 'really surprised that there is no discussion list (e-group) of Internet users about the technical problems of development. Spore publishes all sorts of Internet addresses where...